Subsidizing education in the economic periphery: Another pitfall of regional policies? - Jens Suedekum (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2003)
A very prominent instrument of regional policy is to foster education and human capital for-mation in economically lagging regions. However, this type of regional policy might actually hurt instead of help the recipient areas. The reason is that individual geographical mobility increases with the personal skill level. Through education subsidies, particularly if targeted on relatively high skilled workers, individuals can cross some threshold level of qualification beyond which emigration pays off. Regional policies then result in a human capital flight harmful to individuals remaining in the economic periphery. This fatal result does not hold for policies that focus on the relatively low skilled.
Keywords: H3; F4; R1; 330; Regional Policy; Education Subsidies; Human Capital; Labour Mobility; European Union